Italy’s thrusting gender theory: teaching in schools and effects on young students - Catarinella, Piermauro; Kram, Suhardi; Hashim, Aziz (GADING Journal for the Social Sciences, 2024)
In recent years, in Italy, the concept known as gender theory has permeated various aspects of public life. It spans across TV, radio, newspapers, media, the Internet, schools, universities, science, and political parties. This ideology, also referred to as progressive-liberal ideology, posits that there are no inherent biological differences between men and women; rather, such differences are considered cultural or socially constructed. The theory suggests individuals identify as male or female based on societal education, and they have the freedom to not only choose their own sexuality but also to change it as desired. Gender theory is closely intertwined with the concept of gender identity, which refers to the intimate self-perception that some people might feel about their sexuality. This topic is now being taught to Italian students attending public elementary and high schools. These institutions aim to cultivate an inclusive environment where the rights of non-binary, transgender, LGBTQIA+, gender fluid, and queer individuals must not only be respected but also given the utmost consideration. Public schools are encouraged to adopt the so-called 'free gender registers,' which allow students to select their own sexual identity. The primary objective of this qualitative research is to investigate whether gender theory is based on scientific evidence or if it is purely ideological. Additionally, the research aims to examine its impact on teachers, students, and their parents. The research draws mainly from current Italian newspaper articles (2017-2023) to provide an accurate portrayal of life in Italian schools and the implications for the Italian educational system.